Traces of Ancient Land Use in Cultural Landscapes of Desert Fringes: A Neglected Heritage and Archive - Lucke, Bernhard; Birk, Jago J.; Schörner, Günther; Kouki, Paula; Abu-Jaber, Nizar (Advances in Science, Technology and Innovation, 2023)
Landscapes of desert fringes are often considered degraded: characterized by encroaching desertification and greatly diminished fertility due to poorly adapted land use. Deserted ancient cities have been interpreted as victims of past environmental mismanagement. However, recent research has made it increasingly clear that the man-made desertification narrative is largely fiction and partly a hegemonic discourse connected with colonial mandates and the establishment of modern statehood. Focusing on Jordan as an example, it is shown that numerous traces of past land use have been preserved in the desert fringes. These ancient land use features are an important part of the cultural heritage which is unfortunately rarely considered, although it provides important testimony to past land use practice and its environmental impact. This is illustrated with two examples: (1) In northern Jordan, some soils of the limestone plateaus are stable old land surfaces where remains of past land use accumulated, mainly in form of pottery. Surveys of off-site archaeological material, combined with systematic soil analysis, proved suited to reconstruct patterns of ancient land use. (2) Near Petra, the trained eye can observe a multitude of terrace remains, and there may have not been one slope that was not terraced at some time during antiquity. A case study of several terrace systems found that they are on the one hand suited to control runoff and thus minimize the risk of flash floods, and on the other hand collected sufficient water for runoff-irrigated agriculture. Feces biomarkers indicate manuring with human excrements. Jordan’s cultural landscapes preserved numerous traces of ancient land use activities which are potential archives of environmental and cultural changes. The available evidence suggests that past human impact did in many cases not lead to land degradation, but created oases in the desert.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ancient land use; Cultural landscape; Environmental reconstruction; Manuring; Terracing